IMPLEMENTASI STANDAR PROSES DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMP NEGERI 2 BOYOLALI TAHUN PELAJARAN 2016/2017 - Kurniawan, Taufiq (El-Hayah, 2019)
Abstract:Standard process is a reference in the implementation of learning process to make qualified learning process, so learning goals that have been set can be achieved maximally. This study aims at (1) describing and analyzing steps of teachers in learning Islamic Education at SMP 2 Boyolali. (2) describing and analyzing process of teachers in the implementation of Islamic Education lesson at SMP 2 Boyolali, (3) describing and analyzing techniques applied by teachers in evaluating Islamic Education subject at SMP 2 Boyolali.This research was qualitative research applying descriptive approach. Technique of collecting data used unstructured interviews, non-participant observation, and documentation. Data were analyzed by using interactive model consisting of data collection, data reduction, data display, and conclusion. Checking the validity of the data had been done by increasing the observational persistence and triangulation.The result of this research shows that; (1) Planning of learning Islamic Education and Character subject conducted by teachers is guided by the rules that have been set by the government, such as the preparation of RPP (lesson plan) developed from the syllabus that has been determined for each level. So it can be intended that the RPP is obeyed from the standard rules that set by the central government. (2) Implementation of learning of Islamic Education and Character has been done by teacher refers to process standard which have been determined by government, there is implementation on standard process of learning which have some parts including initial activity, core activity and last activity. (3) Evaluation by teachers of Islamic Education and Character seen from the standard of assessment that has been set in National Education Standard is less in accordance with the rules, such as affective and psychomotor assessment. It is because teachers develop their own instruments to conduct an evaluation. While the cognitive aspect is in accordance with the standards set by the government.Â Â Keywords: Implementation, Standard process